Transcriptome Analysis Reveals Impaired Fertility and Immunity Under Salinity Exposure in Juvenile Grass Carp - Zhang, Jingjing; Wu, Zhi; He, Yujie; Li, Xinhui; Li, Jie (Frontiers in Marine Science, 2021)
Grass carp (Ctenopharyngodon idellus) is one of the most economically important aquaculture species and is widely cultured in China. However, its wild populations in many rivers are increasingly declining, and seawater intrusion is one of the most important threats to their survival. However, the mechanisms underlying the decline due to salinity pressure are still unknown. Here, we performed a comparative transcriptome analysis of C. idellus larvae in response to salinity exposures; a total of 481 differentially expressed genes (DEGs) were identified. These DEGs were significantly enriched in eight Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, among which steroid biosynthesis was the most important one, with the highest enrichment score. The pathway plays an important role in the development of the testes and ovary. Interestingly, all DEGs in steroid biosynthesis showed a down regulation, indicating that salinity exposure may pose damage to the fertility of C. idellus. Furthermore, three immunity-associated pathways (cytokine–cytokine receptor interaction, Toll-like receptor signaling pathway, and NOD-like receptor signaling pathway) were also significantly enriched, suggesting impaired immunity and a high risk of disease infection under salinity exposure. Overall, damage to both fertility and immunity would decrease the number of offspring and increase the risk of death due to disease infection. Our results provide a potential molecular mechanism underlying the decline of wild C. idellus populations in the Pearl River.